Improving The Object Of Fiduciary Guarantee According To Law Number 42 Of 1999 On Fiduciary Guarantee - Ahmad Yani Kosali (Journal of Sustainable Development Science, 2020)
Fiduciary is the transfer of ownership rights of an object based on trust, where ownership right of the object is transferred remains under the control of the owner of the object. The subject of the research was how to bind the object of fiduciary guarantee according to Law Number 42 of 1999 on fiduciary? What are the consequences if the binding of fiduciary guarantee object is unfulfilled? This research was normative legal research which means that the objects are secondary data on library. The type of the research was descriptive. It can be concluded that the binding of fiduciary guarantee object according to Law Number 42 of 1999 on fiduciary guarantee is certificate of fiduciary guarantee as an evidence which is an authentic deed. It can be seen from the characteristics of certificate fiduciary guarantee, issued by an authorized official or public official who has authority for issuing certificate fiduciary guarantee in Fiduciary Registration Office under the supervision of the Ministry of Law and Human Rights. The consequences (the binding of fiduciary guarantee object is unfulfilled) are the default causes several legal consequences for debtors and creditors, especially for creditors who must loss. While for debtors, the legal consequence is the existence of a new status for which the debtor must responsible of. Fiduciary guarantee, mostly in form of movable objects, allows for a transfer of fiduciary guarantee; one example of the reason for the transfer is the debtor wants to transfer his credit to another creditor to seek for lower interest. Then, if a debtor has paid off the debt, it can cause the fiduciary guarantee to be canceled.